Complete recovery of restless legs syndrome after unilateral thalamic and tegmental infarction: A case report. (October 2017) - Cogez, Julien; Ribeiro, Espartaco; de La Sayette, Vincent; Viader, Fausto
Highlights: Substantially less is known about neuroanatomic basis of restless leg syndrome. Restless leg syndrome can be triggered or cured by a stroke. The thalamus and the tegmentum could have a role in the genesis of symptoms.